Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1245/s10434-012-2607-9
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Immediate Breast Reconstruction After Mastectomy: Impact of State and Federal Health Policy Changes

Abstract: Rates of IBR increased across all racial groups after policy changes. However, not all races were affected equally, and thus disparities remained. Future studies are needed to investigate the role of other factors, including cultural preferences in utilization of IBR that might explain residual disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 30 publications
1
31
0
1
Order By: Relevance
“…Our findings extend other studies that have identified disparities in receipt of breast reconstruction 1024 by demonstrating not only that the gap in receipt of reconstruction is evident in a contemporary patient cohort but also that the disparity has not narrowed over time. Given the known benefits associated with receipt of immediate breast reconstruction, 14 it is critical that we as a surgical community move beyond simply describing that sociodemographic factors are associated with disparate care to understanding how these factors lead to the gaps in care in order to improve the quality of breast cancer care for disadvantaged patient populations.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our findings extend other studies that have identified disparities in receipt of breast reconstruction 1024 by demonstrating not only that the gap in receipt of reconstruction is evident in a contemporary patient cohort but also that the disparity has not narrowed over time. Given the known benefits associated with receipt of immediate breast reconstruction, 14 it is critical that we as a surgical community move beyond simply describing that sociodemographic factors are associated with disparate care to understanding how these factors lead to the gaps in care in order to improve the quality of breast cancer care for disadvantaged patient populations.…”
Section: Discussionsupporting
confidence: 85%
“…1024 Our model, adapted from the Behavioral Change Wheel, 31 posits that whether or not a patient undergoes reconstruction is determined by her Capability , Motivation , and Opportunity (Figure 2). Capability includes clinical factors that determine whether a patient is a good candidate for reconstruction, such as recommendation for post-mastectomy radiation or active smoking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the reported rate of synchronous breast cancer is less than 1%, we made the assumption that nearly all the bilateral mastectomies performed had one side that was prophylactic. [17][18][19] Conclusions Despite the higher risks for complications associated with BM and IBR and despite the availability of breast conservation therapy, rates of BM and associated IBR have been rising since 2005. Younger white patients are most likely to choose the most aggressive surgical management of their breast cancer and subsequent reconstruction.…”
Section: Commentsmentioning
confidence: 99%